Notice of Two Pieces of Roman Sculpture found at Arniebog, Dumbartonshire, in June 1868 (With Photogrphs of the Sculptures.) (Proceedings of the Society of Antiquaries of Scotland, 1871)
A description of two sculptured stones discovered by a local farmer in 1868 near to a watch-tower on the Antonine Wall. The stones show two sculptured figures: Neptune and another figure that the author suggests could be a British captive. He argues that this sculptured stone may have been created by the Second Legion, based on the art style, subject choice and the location of the finds. He also describes similar sculptured slabs from the area and provides some general information about the outposts on the Antonine Wall.